Composição nutricional e índice glicêmico de feijões caupi (Vigna unguiculata L. Walp) alvos para biofortificação - Silva, Livia Maria da (2022)
The consumption of foods with a high glycemic index is associated with changes in blood glucose, which can cause metabolic complications throughout the organism. The search for foods associated with functional benefits has been promoting changes in the population's eating habits, especially for foods of vegetal origin, as they have phenolic compounds in their composition and also fibers that are associated with the reduction of the glycemic index of foods. Therefore, the present study aims to evaluate the nutritional composition and glycemic index of cowpea (Vigna unguiculata L. Walp) targets for biofortification. Cowpea varieties target for biofortification were used in the study BRS Xique-xique, BRS Aracê and BRS Tumucumaque; and a conventional variety: BRS Pajeú. The beans were cooked in a domestic electric pressure cooker with water (proportion of 1:2, beans and water), freeze-dried and ground to obtain a fine flour. Subsequently, were carried out analyzes of moisture, ashes, proteins, carbohydrates, lipids, dietary fibers, minerals phenolic compounds, and antioxidant activity. After the chemical analysis, the glycemic index and glycemic load of the beans were evaluated.This evaluation was performed through an acute study with eleven healthy volunteers, who ingested each of the 4 cowpea beans mentioned above and three doses of the anhydrous glucose control, containing 25 g of available carbohydrates, on non-consecutive days. During a period of 120 minutes, the postprandial glycemic response was verified. The chemical composition data were analyzed by ANOVA and Tukey's test (p<0.05). The present study was approved by the Research Ethics Committee of UFES (nº 5.181.338). The results showed a high amount of total dietary fiber in the beans (between 22.7 ± 1.29 and 36.07 ± 1.08 g/100g) the predominant insoluble fiber (between 20,52 ± 0,96 and 30,22 ± 1,08), BRS Pajeú presented the highest value. The phytate content in BRS Pajeú and BRS Xiquexique was similar (0.97 ± 0.02g/100g) with higher values in relation to cultivars BRS Tumucumaque (0.89 ± 0.01g/100g) and BRS Aracê (0 .66 ± 0.02g/100g). The iron content in BRS Xique-xique (50.82 ± 1.95mg/kg) was higher, showing similarity between the cultivars BRS Pajeú (50.68 ± 0.46mg/kg) and BRS Aracê (46.72 ± 3 .30mg/kg), while BRS Tumucumaque had the lowest value (44.66 ± 1.66mg/kg). As for the glycemic index, all beans had a smaller incremental area under the glycemic curve (iAUC) compared to the glucose area. BRS Pajeú (1520 ± 331.6 mg/dLx min) obtained an iAUC value similar to BRS Xique-xique (1215 ± 382.9 mg/dL x min), however the value found was higher compared to BRS Tumucumaque (1090 ± 333.9 mg/dL x min) and BRS Aracê (612.7 ± 318.1 mg/dL x min). The glycemic index of BRS Aracê (25.89 ± 0,83) was the lowest value obtained among cowpea beans, followed by BRS Tumucumaque (46.05 ± 0,88), BRS Xique-xique (51.33 ± 1,00) and BRS Pajeú (64.22 ± 0,87). The values of glycemic load BRS Aracê (4.70) had the lowest value followed by BRS Pajeú (5.10), BRS Tumucumaque (7.32) and BRS Xique-xique (8.26). Regarding the sensory parameters, only the taste and texture showed a statistically significant difference, with BRS Pajeú and BRS Xique-xique being different from each other. It is concluded that cowpeas targeted for biofortification had the lowest glycemic index, which could be a low-cost alternative to improve the quality of the population's diet.